AN ANALYSIS OF GENERALIZED SYMMETRICAL COMPONENTS IN NON SINUSOIDAL THREE PHASE SYSTEMS - Hungaro Costa, Leandro Luiz [UNESP]; Amaral Serni, Paulo Jose [UNESP]; Marafao, Fernando Pinhabel [UNESP]; IEEE (Ieee, 2011)
This paper presents the study of the so called Generalized Symmetrical Components, proposed by Tenti et. al. to the analysis of unbalanced periodic non sinusoidal three phase systems. As a result, it was possible to establish a proper relationship between such of generalized symmetrical components and Fortescue symmetrical components to the harmonic frequencies that compose a generic periodic non sinusoidal three phase system.
Keywords: Generalized Symmetrical Components; Symmetrical Components; Harmonic; Unbalance; Non Sinusoidal